1988
DOI: 10.1007/bf01321480
|View full text |Cite
|
Sign up to set email alerts
|

Differences in physician prevention practice patterns for white and minority patients

Abstract: A telephone survey of 120 randomly selected primary care physicians in New York City was completed in October, 1984 (response rate = 90%) concerning physicians' recommendations for health promotion and disease prevention. Responses from physicians with 50% or more Black and Hispanic patients were compared with responses from physicians with 50% or more White patients. The former were found to be less likely to follow guidelines from nationally recognized organizations for health promotion and disease preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
2

Year Published

1991
1991
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(44 citation statements)
references
References 7 publications
1
41
2
Order By: Relevance
“…Poverty has a negative impact on the behavior of health care providers and the availability of health services (40). Those who provide health care for minorities and people in lowincome areas, for example, are often less informed about preventive care services and are less likely to be board certified (84,85). Physicians who are not board certified show lower compliance with appropriate screening recommendations (86,87).…”
Section: Barriers Related To Povertymentioning
confidence: 99%
“…Poverty has a negative impact on the behavior of health care providers and the availability of health services (40). Those who provide health care for minorities and people in lowincome areas, for example, are often less informed about preventive care services and are less likely to be board certified (84,85). Physicians who are not board certified show lower compliance with appropriate screening recommendations (86,87).…”
Section: Barriers Related To Povertymentioning
confidence: 99%
“…Being poor and in poor health is a form of double jeopardy that affects many unemployed, underemployed, and black people lacking medical insurance who may use the health-care system only when faced with a crisis. One study indicated that physicians with predominantly black or Hispanic patient populations were significantly less likely to recommend preventive practices and screening tests compared with physicians with predominantly white patient populations (11). Cultural values and poverty.…”
Section: Potential Barriersmentioning
confidence: 99%
“…[37][38][39][40] In this study, women whose regular physician was an obstetrician-gynecologist reported a physician recommendation more often than did other women, although fewer than 10% of the women reported that their regular physician was an obstetrician-gynecologist. Recommendation likely varies by physician characteristics and attitudes, 41 but this analysis was not able to consider physicians'characteristics other than specialty. Women's preferences for mammography also may affect physician recommendation of the procedure, but this study did not measure women's preferences.…”
Section: Discussionmentioning
confidence: 99%